Digital Storytelling to Improve Learners’ Motivation in Learning Speaking - Setiyorini, Tri Jampi (Institut Agama Islam Negeri Palopo, 2025)
The Independence curriculum provides various skills – listening, reading, speaking, and writing. However, many students lack motivation to learn speaking due to inadequate ideas, lack of self-confidence, and uninteresting learning media. On the contrary, motivation has a crucial role in English learning. This study aims to find out whether digital storytelling can increase learners' motivation to learn to speak. The method used is a descriptive case study. The research participants were 36 learners of Class X Social 1 in a private Islamic senior high school, Central Java, Indonesia. Data were collected by using close-ended questionnaires and focus group interviews. The research results showed a significant improvement of learners’ motivation in learning speaking after using digital storytelling. The questionnaire results showed that students' intrinsic motivation is higher than their extrinsic motivation. It can be proved that 55.56%-66.67% of students agree and 11.11%-22.22% of students strongly agree with all statements about intrinsic motivation in learning speaking. Interview results showed that learners' intrinsic motivation in learning speaking is high. Therefore, digital storytelling can increase students' motivation to learn to speak.